2018
DOI: 10.1111/gcb.14042
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotes in the WAIS Divide ice core reflect source and transport changes between Last Glacial Maximum and the early Holocene

Abstract: We present the first long-term, highly resolved prokaryotic cell concentration record obtained from a polar ice core. This record, obtained from the West Antarctic Ice Sheet (WAIS) Divide (WD) ice core, spanned from the Last Glacial Maximum (LGM) to the early Holocene (EH) and showed distinct fluctuations in prokaryotic cell concentration coincident with major climatic states. The time series also revealed a ~1,500-year periodicity with greater amplitude during the Last Deglaciation (LDG). Higher prokaryotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 137 publications
(164 reference statements)
2
23
0
Order By: Relevance
“…2D). High-latitude open water and sea ice are rich in microbial communities, components of which may be collected by passing storms and delivered onto the ice sheet (e.g., prokaryotes, DNA), offering insights into offshore environmental processes (51,52). To investigate environmental changes prior to and after the ice sheet reconfiguration recorded in the Patriot Hills BIA, we applied an established ancient DNA methodology and sequencing to provide a description of ancient microbial species preserved within the ice (Methods).…”
Section: Ocean Warmingmentioning
confidence: 99%
“…2D). High-latitude open water and sea ice are rich in microbial communities, components of which may be collected by passing storms and delivered onto the ice sheet (e.g., prokaryotes, DNA), offering insights into offshore environmental processes (51,52). To investigate environmental changes prior to and after the ice sheet reconfiguration recorded in the Patriot Hills BIA, we applied an established ancient DNA methodology and sequencing to provide a description of ancient microbial species preserved within the ice (Methods).…”
Section: Ocean Warmingmentioning
confidence: 99%
“…Bulk measurements of cell levels have previously been obtained in natural glacial ice systems and were determined to be between 10 2 and 10 8 cells/mL (Mader et al, 2006;Miteva et al, 2009;Santibáñez et al, 2018). However, what is unaccounted for in these measurements is the submillimeterto centimeter-scale spatial heterogeneity in the distribution of cells within the ice.…”
Section: Implications For Detecting Cells In Natural Glacial Systemsmentioning
confidence: 99%
“…O nce considered inhospitable to life, in recent decades icy environments on Earth have been found that preserve organic material and even harbor active microbial communities (Priscu et al, 1998(Priscu et al, , 1999Siegert et al, 2001;Priscu, 2005;Santibáñez et al, 2005Santibáñez et al, , 2018Krembs et al, 2011;Uhlig et al, 2015). Glacial ice on Earth is known to contain organic material (Barnes et al, 2003;Barletta et al, 2012), including bacteria, algae, viruses, plant fragments, pollen grains, and black carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Riverine fluxes have long been recognized as an important source of carbon and nutrients to the oceans (Meybeck, 1982), with high fluxes of dissolved organic carbon (DOC) occurring at low latitudes (0-30°; 62% of total known global inputs) and northern high latitudes (60-90°; 19%) (Dai et al, 2012). Polar ice sheets and glaciers, which store~70% of the Earth's fresh water have only recently been identified as important repositories of organic matter (Hood et al, 2015;Lawson et al, 2014;Santibáñez et al, 2018) and biologically important nutrients (Bhatia et al, 2013;Dubnick et al, 2017;Hawkings et al, 2016;Wadham et al, 2016) that can be exported to marine environments. The Greenland Ice Sheet is thought to dominate the fluxes from large ice sheets due to its high rate of glacier mass turnover via surface (supraglacial) melt and iceberg calving (Hood et al, 2015); however, the absence of data from the Antarctic ice sheet (AIS) has prevented meaningful comparison between the worlds' major ice sheets.…”
Section: Introductionmentioning
confidence: 99%